Sulforaphane in alternative cancer chemotherapy: From carcinogenesis suppression to drug resistance reversal - Seyed Mohammad Doodmani; Payman Rahimzadeh; Najma Farahani; Seyedalireza Mirilavasani; Mina Alimohammadi; Noushin Nabavi; Elmira Alaei; Afshin Taheriazam; Maryam Abedi; Nadia Shafiee; Salman Daneshi; Mehrdad Hashemi (Results in Chemistry)
The management and treatment of cancer have posed significant challenges in recent years. Conventional chemotherapy, despite its widespread use, has encountered obstacles such as the emergence of drug resistance. As a result, natural products have gained considerable attention as alternative therapies for cancer treatment. These compounds can also be combined with chemotherapy drugs to enhance tumor suppression. Sulforaphane (SFN), a bioactive compound derived from broccoli, has demonstrated remarkable health-promoting properties, including antioxidant, anti-inflammatory, and antidiabetic effects. This review focuses on SFN’s role in cancer treatment, emphasizing its biological mechanisms and ability to regulate drug resistance. Key mechanisms discussed include the regulation of cell death pathways, such as apoptosis, ferroptosis, and autophagy, which are critical in cancer therapy. Additionally, SFN’s ability to suppress metastasis and impair the epithelial-to-mesenchymal transition (EMT) mechanism is highlighted. By inhibiting glycolysis, SFN can reduce the energy supply required for cancer cell proliferation. When combined with chemotherapy drugs, SFN enhances tumor suppression and mitigates drug resistance in human cancers. This is achieved primarily by promoting apoptosis, reducing proliferation, and inhibiting metastasis. In conclusion, SFN shows significant promise in cancer therapy by targeting multiple molecular pathways, improving the efficacy of chemotherapy, and overcoming drug resistance, particularly when incorporated into advanced nanoparticle delivery systems.